Pengaruh Lokasi, Persepsi Harga dan Daya Tarik Wisata Terhadap Keputusan Berkunjung di Pura Mangkunegaran Surakarta - Felix Rajendra Adiyatma; Retno Susanti (Teewan Journal Solutions, 2026)
This study is a survey of tourists visiting Mangkunegaran Palace in Surakarta regarding the influence of location, price perception, and tourist attraction at Mangkunegaran Palace on the decision to visit, using a quantitative approach. The reason this location is the subject of this study is because the issues surrounding the location, price perception, and tourist attraction of Mangkunegaran Palace in Surakarta are interesting to study. The type of data used in this study is quantitative data, and the data source in this study uses primary data. The primary data in this study is the number of tourists visiting Mangkunegaran Palace in Surakarta through questionnaires. The number of samples in this study is not known precisely, so Paul Leedy's formula was used with 100 respondents. The sampling method used was purposive sampling, which is sampling with certain criteria. The data analysis technique used descriptive analysis and inductive analysis, consisting of multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results of this study indicate that the variables of location, price perception, and tourist attraction have a positive effect on tourists' decision to visit Mangkunegaran Palace in Surakarta. For further research, it is hoped that the author can use variables that have not been used in this study and employ more varied data collection techniques and methods.